The Impact of a Vitamin C + D Cream Combination on Striae Distensae in Primipara: A Randomized Controlled Clinical Trial Investigation - Hadis Taheri; Masoomeh Kheirkhah; Ali Ghobadi; Nooshin Eshraghi; Shima Haghani (Clinical and Experimental Obstetrics & Gynecology)
Background: Pregnancy striae, a common problem in pregnant women, create significant concerns about beauty in most women and there are challenges in preventing and treating them. The current research sought to investigate the impact of a vitamin “C + D” cream combination on striae distensae in primipara. Methods: The current research was a clinical study with a control group, which was carried out in parallel with 60 primipara at 18–20 weeks gestational age, who presented at Shahid Akbarabadi Hospital in Tehran between 20/07/2022 to 20/01/2023. Sampling was done using a continuous method, and then allocated into two groups using a random block of 4 and 8 with the Sealed Envelope online software. One group received vitamin “C + D” cream (30 candidates) while the other group received a placebo cream (30 candidates). Both sets of candidates applied the creams to the skin of the abdomen, breasts, thighs, and hips twice daily for four months. Evaluation of the severity and quantity of stretch marks was performed with the Atwal’s numerical tool scale. An assessment was conducted by the investigator at the study center’s prenatal clinic before and at 4, 8, 12, and 16 weeks following the intervention. Results: There were no notable disparities in individual and obstetrical characteristics between groups before the intervention (p > 0.05). Both the intervention and control groups did not have any striae before the intervention. After 4 weeks of intervention, no striae were observed in the combination cream group, while 50% of individuals in the control group had mild striae. After 8 weeks, no striae were observed in the combination cream group, while 50% of the control group had mild striae. After 12 weeks of intervention in the vitamin C and D group, only 16% of individuals had mild striae, while in the control group, 50% had mild striae and 16.67% had moderate striae. After 16 weeks of intervention, in the intervention group, 16% of individuals had mild striae, while in the control group, 50% had mild striae and 33.33% had moderate striae. There was a noticeable disparity in the development of pregnancy striae between the two groups at every point of observation. The vitamin C and D cream demonstrated efficacy in diminishing the appearance and intensity of striae in pregnancy, as well as impacting the timing of their appearance (p < 0.001). Conclusions: Given the positive outcomes of utilizing combination of vitamin C and D to prevent pregnancy striae, along with its cost-effectiveness, safety, and reception among pregnant women, it is advisable for the prevention of striae during pregnancy. Clinical Trial Registration: The study has been registered on https://trialsearch.who.int/ (registration number: IRCT20220509054799N1; the trial was registered on 06/06/2022).